FLOWING OF THE FEMININE; GROUNDING OF THE MASCULINE: EXPLORING SEXUAL DIFFERENCE AND FAMILIAL HARMONY IN KUMBALANGI NIGHTS THROUGH THE LENS OF LUCE IRIGARAY - S Krishna, Arabhi; Devi K (International Journal of Research -GRANTHAALAYAH, 2025)
This paper critically analyzes the 2019 Malayalam film Kumbalangi Nights through the lens of Luce Irigaray’s theory of sexual difference. The film’s narrative challenges rigid patriarchal gender roles by contrasting the hypermasculinity of the character Shammi with the emotional evolution of four estranged brothers who gradually embrace vulnerability, care, and mutual interdependence. Drawing on Irigaray’s critique of phallocentric structures and her call for relational ethics rooted in gender difference, this study argues that Kumbalangi Nights envisions family harmony not through erasure of gender roles but through their fluid integration. The paper highlights how the film subverts dominant cinematic and cultural portrayals of masculinity and femininity, offering an alternative vision where coexistence, emotional expression, and respect for difference pave the way for healing and transformation within the family. Through qualitative analysis and close reading of key scenes, this work situates the film within broader feminist and philosophical discourses, emphasizing the relevance of Irigaray’s ideas in contemporary cinematic narratives.